(untitled) (Revista Apotheke, 2021)
This article is an experience report on the potentialities of the Lumière Minute, an audiovisual resource inspired by the Lumière Brothers’ geminal cinematographic productions, as an instrument of evaluation of the discipline "Evolution"of a Bachelor of Science course in Biological Sciences, which the offer took place remotely because of the COVID-19 pandemic. The students of the discipline, after technical-conceptual guidance on the device, produced and socialized their Lumière Minute with the theme of Human Evolution, which was one of the evaluations of the discipline and presented the vision of that scientific knowledge from the perspective of students, constituting a viable and multilevel for learning in evolutionary biology.